The Meaning-Making of Gender Identity Transition in Individual with Hypospadias - Raina Xexine Purwitasari; Desi Dwi Prianti (Jurnal Ners, 2025)
This study explores the gender identity transformation of Aprilio Manganang, a former national volleyball athlete who has hypospadias, a medical condition where the urethra does not extend to the tip of the penis. For 28 years, Aprilio lived as a female despite lacking female hormones or organs. The study utilizes Relational Dialectic Theory and Alfred Schutz's phenomenological approach to understand Aprilio's interpersonal communication during his gender transition process. Data were collected through in-depth interviews and observations conducted over 2 days at Aprilio Manganang's residence. Interviews were conducted with Aprilio Manganang, family members, and colleagues. The results of the study indicate that Aprilio's gender transformation involves significant symbolism such as name changes, medical procedures, and institutional support, which strengthen his gender identity as male. Social interactions with family, friends, and colleagues also play a crucial role in the acceptance and affirmation of his new gender identity. This research fills a research gap by examining the social and communication aspects of individuals with hypospadias, providing a deep understanding of the challenges and strategies in facing social discrimination and stigma. These findings highlight how an individual with a gender identity transition faces the primary dialectic between the gender identity they internally perceive as male and the social expectations and perceptions that compel them to be female.